Perlindungan Hukum Perempuan Korban Pelecehan Seksual di Kereta Commuter Indonesia (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines legal protection for women who become victims of sexual harassment in commuter rail services operated by PT Kereta Commuter Indonesia. The issue is significant because mass public transportation can expose female passengers to repeated risks of harassment, while consumer protection principles require service providers to ensure safety, comfort, and proper complaint handling. Using normative juridical research with a statutory approach, the article reviews the relationship between consumer protection law, railway regulation, witness and victim protection law, and the practical measures adopted by KAI Commuter. The study finds that KAI Commuter has taken preventive and responsive steps, including women-only carriages, complaint channels, campaign activities, and support for reporting. However, implementation is still not fully optimal because users continue to experience harassment and victim support facilities remain limited. The article argues that stronger preventive systems, clearer sanctions, and more integrated victim assistance are necessary to make legal protection in commuter rail services more effective.
Keywords: Sexual Harassment; Women Passengers; Commuter Rail; Consumer Protection; Victim Assistance